Home Ownership : Getting in, Getting from, Getting Out. - Boelhouwer, P. (Housing and Urban Policy Studies, v. 29., 2005)
Drawing from the Conference on Housing Growth and Regeneration, this book talks about the gains and losses accruing to individual households by virtue of their position as home owners. It also focuses on the losses, in the form of repayment risk, related to, difficulties that households may experience in meeting housing loan repayment schedules.